THE METABOLIC DISORDERS AND CARDIOVASCULAR RISK AMONG LOWER SOCIOECONOMIC SUBJECTS IN YOGYAKARTA-INDONESIA - Suhadi, Rita; Linawati, Yunita; Wulandari, Erna Tri; VIRIGINIA, DITA MARIA; Setiawan, Christianus Heru (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: The prevalence of hypertension, diabetes mellitus, dyslipidemia, and obesity in developing countries was high regardless the socioeconomic status, whereas the awareness and the control of these metabolic disorders were inadequate. The aim was to compare the cardiovascular risk based on numbers of metabolic disorders among lower socioeconomic subjects. Methods: The study was done with the analytical cross-sectional method. The subjects were selected with cluster random sampling from four villages. We included the subjects of 30-65 years old and signed the informed consent but excluded the subjects who had not fasted for 8-10 hrs. We analyzedÂ the cardiovascular parameters among groups with ANOVA statistics, the difference between actual and heart vascular age (HVA) with paired t-test,Â and the change of six cardiovascular parameters with radar diagram.Â Results: The eligible subjects (n=222) comprised 0-4 metabolic disorders at 25.2%, 33.8%, 28.8%, 9.9%, and 1.8%, respectively; with age atÂ 50.1Â±9.0 years; body mass index (BMI) 24.1Â±4.8 kg/m2; blood pressure (BP) 141.6Â±23.4/82.8Â±11.7 mmHg; fasting blood sugar (FBS) 98.7Â±37.4 mg/dL;Â total and high-density lipoprotein cholesterol 201.0Â±37.9 and 55.1Â±12.7 mg/dL; Framingham score was 11.4Â±8.9% (referred as medium risk); theÂ difference between actual and HVA at 13.2Â±13.0 (p<0.05). Increasing metabolic disorders lead to higher BP, FBS, cholesterol, Framingham score, andÂ the difference between actual and HVA (p<0.05) excluding BMI in the four metabolic disorder subgroup. Conclusion: The subjects had the medium cardiovascular risk with above normal BMI, BP, and total cholesterol profiles. The average age, BP, FBS, cholesterol, Framingham score, and HVA were likely to increase equivalent to the numbers of metabolic disorders. Keywords: Hypertension, Diabetes mellitus, Dyslipidemia, Obesity, Cardiovascular risk, Metabolic disorders.